2018
DOI: 10.1038/s41598-018-19506-8
|View full text |Cite
|
Sign up to set email alerts
|

A new class of magnetically actuated pumps and valves for microfluidic applications

Abstract: We propose a new class of magnetically actuated pumps and valves that could be incorporated into microfluidic chips with no further external connections. The idea is to repurpose ferromagnetic low Reynolds number swimmers as devices capable of generating fluid flow, by restricting the swimmers’ translational degrees of freedom. We experimentally investigate the flow structure generated by a pinned swimmer in different scenarios, such as unrestricted flow around it as well as flow generated in straight, cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…57 The Purcell 3-link swimmer is capable of producing tuneable flow rates when altering the phase difference of the two hinges, 49,50,58,59 and has been theorised to be capable of producing flow in the reverse direction, 60 however achieving reverse flow rates in this manner is experimentally impractical as it would require high amplitude deformation which has not yet been achieved experimentally. Hamilton et al 20 has shown that placing restrictions on the near-field fluid vortices around an elastomagnetic pump can constrain the resultant fluid flows into producing strong flow in the negative direction without altering the motion of the pump. In this manner, the flow direction can be controlled through much smaller changes in pump behaviour.…”
Section: Working Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…57 The Purcell 3-link swimmer is capable of producing tuneable flow rates when altering the phase difference of the two hinges, 49,50,58,59 and has been theorised to be capable of producing flow in the reverse direction, 60 however achieving reverse flow rates in this manner is experimentally impractical as it would require high amplitude deformation which has not yet been achieved experimentally. Hamilton et al 20 has shown that placing restrictions on the near-field fluid vortices around an elastomagnetic pump can constrain the resultant fluid flows into producing strong flow in the negative direction without altering the motion of the pump. In this manner, the flow direction can be controlled through much smaller changes in pump behaviour.…”
Section: Working Principlesmentioning
confidence: 99%
“…12 Generating net motion in the Stokes regime has been a lively area of study over the last few decades, underpinned by the work of Purcell 13 and Taylor, 14 and has grown into a diverse field with a multitude of swimming and pumping mechanisms being developed both theoretically and experimentally. Research in this field has explored a vast array of driving mechanisms, including magnetic torque, [15][16][17][18][19][20][21][22][23] electric fields, 24,25 light, 26,27 acoustic waves [28][29][30] and chemical energy. [31][32][33] Many of these driving mechanisms have been studied in the context of microscopic pumping solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such a manipulation has been typically addressed by developing complex microfluidic devices with moving structures and using bulky, specialized, and expensive peripherals, which also often require technically skilled users. A myriad of other integrated liquid control strategies, including manual (8), electrical (9), chemical (10), optical (11), magnetic (12), and thermal (13) actuation, have been developed, but they generally lack programmability and real-time feedback and still suffer from fabrication complexities and known issues associated with high-throughput manufacturing and integration of polydimethylsiloxane (PDMS) and hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Once activated with an oscillating magnetic field, the ferromagnetic swimmer is able to swim in liquid or pump fluids at a low Reynolds number regime. The devices have been successfully demonstrated experimentally [14], [15], however, the designs were implemented at a millimeter scale with the magnetic elements constructed using bulk materials (e.g. NdFeB magnets).…”
Section: Introductionmentioning
confidence: 99%